ANALYSIS OF ANGRY EXPLOSIONS IN DELI MALAY: A STUDY OF NATURAL SEMANTIC METALANGUAGE - Wulan, Eka Putri; Mulyadi, Mulyadi (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
This study aims to describe and analyze the meaning of swear words in Deli Malay through the theory of Natural Semantic Metalanguage (MSA). The focus of the study is directed at the forms of metaphors and allusions that represent the expression of anger of the Deli Malay community in the city of Medan and its surroundings. The data studied are in the form of oral speech obtained from native speakers aged over 40 years who use BM Deli in everyday life. The data collection technique was carried out using the listening method, with advanced techniques in the form of listening with conversation and listening without conversation. Data analysis was carried out using the MSA-based semantic element and explication separation technique to reveal the original meaning of each form of swearing. The results of the study show that angry swearing in Deli Malay does not only function as an emotional release, but also as a reflection of the local cultural value and cognition system. The swearing systematically utilizes linguistic references such as body parts, kinship terms, animals, professions and social activities, which have the meaning of “bad”, “doing”, “feeling”, “knowing”, and “happening” in the original meaning structure. The MSA theory makes an important contribution in identifying universal meaning elements and at the same time explaining cultural specificities in the linguistic expressions of the Deli Malay community. Thus, this study strengthens the position of MSA as an effective theory in explaining the relationship between language, emotion, and culture from a cross-linguistic semantic perspective.